Fever following Covid‐19 vaccination in subjects with Brugada syndrome: Incidence and management. (21st June 2022) - Santoro, Francesco; Crea, Pasquale; Pellegrino, Pier Luigi; Cetera, Rosa; Gianfrancesco, Domenico; Abumayyaleh, Mohammad; Giuseppe, Dattilo; Allegra, Marta; Mancini, Nastasia; D'Arienzo, Girolamo; Mȕgge, Andreas; Aweimer, Assem; et al.
Abstract: Background: Fever is a potential side effect of the Covid‐19 vaccination. Patients with Brugada syndrome (BrS) have an increased risk of life‐threatening arrhythmias when experiencing fever. Prompt treatment with antipyretic drugs is suggested in these patients. Aim of the study: To evaluate the incidence and management of fever within 48 h from Covid‐19 vaccination among BrS patients. Methods: One hundred sixty‐three consecutive patients were enrolled in a prospective registry involving five European hospitals with a dedicated inherited disease ambulatory. Results: The mean age was 50 ± 14 years and 121 (75%) patients were male. Prevalence of Brugada electrocardiogram (ECG) pattern type‐1, ‐2, and ‐3 was 32%, 44%, and 24%, respectively. Twenty‐eight (17%) patients had an implantable cardioverter‐defibrillator (ICD). Fever occurred in 32 (19%) BrS patients after 16 ± 10 h from vaccination, with a peak of body temperature of 37.9° ± 0.5°. Patients with fever were younger (39 ± 13 vs. 48 ± 13 years, p = .04). No additional differences in terms of sex and cardiovascular risk factors were found between patients with fever and not. Twenty‐seven (84%) out of 32 patients experienced mild fever and five (16%) moderate fever. Pharmacological treatment with antipyretic drugs was required in 18 (56%) out of 32 patients and was associated with the resolution of symptoms. No patient required hospital admission and no arrhythmic episode was recorded in patients with ICD within 48 h after vaccination. No induced type 1 BrS ECG pattern and new ECG features were found among patients with moderate fever. Conclusion: Fever is a common side effect in BrS patients after the Covid‐19 vaccination. Careful evaluation of body temperature and prompt treatment with antipyretic drugs may be needed.